On some I -convergent generalized difference sequence spaces associated with multiplier sequence defined by a sequence of modulli - Debnath, Shyamal; Saha, Subrata (Proyecciones (Antofagasta), 2025)
In this article we introduce the sequence spaces cI (F, Λ, Δm,p), coI (F, Λ, Δm,p) and ℓ ∞I (F, Λ, Δm,p), associated with the multiplier sequence Λ = (λk), defined by a sequence of modulli F = (f k). We study some basic topological and algebraic properties of these spaces. Also some inclusion relations are studied.